Modified silica powder as well as preparation method and application thereof
By combining silicon powders of different particle sizes and modifying the problem of silicon powders prone to agglomeration and introduction of impurities in silicon rubber, the high thermal conductivity and high electrical conductivity of silicon rubber composite materials are achieved.
Patent Information
- Application Number
- CN202510838231.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-08-26
AI Technical Summary
Silicon powder is prone to agglomeration and poor dispersion in organic polymers, and impurities are easily introduced during the grinding process, affecting its thermal and electrical conductivity in silicon rubber.
Two silicon micropowders of different particle sizes are combined and surface modified by a modifier solution, including spray treatment of polymer solution and coupling agent, forming a tight thermal conductivity network to improve interface compatibility and electrical conductivity.
Improve the thermal conductivity and electrical conductivity of silicone rubber composites at low filling amounts, while maintaining good mechanical properties and electrical insulation properties.
Smart Images

Figure BDA0005461312370000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inorganic materials, and in particular to modified silicon micropowder, a preparation method thereof and an application thereof. Background Art
[0002] Silicone rubber, with its Si-O backbone structure, is a high-performance elastomeric material with excellent properties, including resistance to high and low temperatures, high pressure, ozone aging, radiation, weathering, physiological inertness, breathability, and solvent resistance. It is an essential advanced material widely used in aerospace, defense, electronics, machinery manufacturing, construction, petrochemicals, healthcare, and other fields. Its excellent high-temperature and solvent resistance and processing properties make it a preferred polymer matrix for thermally conductive polymer composites. In the field of new energy batteries, silicone rubber plays an indispensable role in battery packaging, battery / electrode protection, and cable insulation. However, silicone rubber has poor thermal conductivity, with a coefficient of only 0.2 W / m·K. This can hinder the timely dissipation of heat generated by electronic devices, thereby reducing the reliability and service life of electronic components. Therefore, large amounts of thermally conductive fillers are often added to improve the thermal conductivity of silicone rubber.
[0003] Silica powder is a white, non-toxic, ultrafine powder primarily composed of silicon dioxide. It exhibits excellent physical properties, chemical stability, high-temperature resistance, and thermal conductivity, making it widely used in packaging fillers, coatings, and semiconductor devices. Compared to other fillers, silica powder offers significant advantages in terms of reinforcement, thermal conductivity, and electrical conductivity for silicone rubber, and it also exhibits excellent dispersibility in silicone rubber. However, during the ultrafine refinement process, as its specific surface area increases, a large number of hydroxyl (-OH) groups are exposed on the surface of the silica powder, increasing its surface polarity. Furthermore, static electricity can lead to agglomeration between silica powder particles, severely impacting its dispersion in organic polymers. Furthermore, due to its high hardness, strong toughness, and poor grindability, conventional mechanical grinding methods consume high energy and have low production capacity. Furthermore, the grinding process can easily introduce impurities from other components, reducing the purity of the silica powder and causing secondary contamination.
[0004] Therefore, providing a preparation method of silicon micropowder that can improve surface polarity without introducing impurities is of great significance for the wide application of silicon micropowder. Summary of the Invention
[0005] The purpose of the present invention is to provide a modified silicon micropowder and a preparation method and application thereof in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing modified silicon micropowder, comprising the following steps:
[0008] 1) Dry grinding the quartz ore particles to obtain ordinary silicon powder;
[0009] 2) Wet ball milling of ordinary silicon powder to obtain ultrafine silicon powder;
[0010] 3) Ordinary silicon micropowder, ultrafine silicon micropowder and modifier solution are mixed and surface modified to obtain modified silicon micropowder.
[0011] Preferably, the diameter of the quartz ore particles in step 1) is 5 to 10 cm, and the D50 particle size of ordinary silicon powder is 16 to 19 μm.
[0012] Preferably, the medium used in the wet ball milling in step 2) comprises sodium polyacrylate, sodium hexametaphosphate and water, wherein the mass of the sodium polyacrylate is 9-12‰ of the mass of ordinary silicon micropowder, the mass of the sodium hexametaphosphate is 4-7‰ of the mass of ordinary silicon micropowder, and the mass of the water is 5-10% of the mass of ordinary silicon micropowder;
[0013] The rotation speed of the wet ball mill is 60-80 r / min, and the time of the wet ball mill is 100-150 min.
[0014] Preferably, the D50 particle size of the ultrafine silicon powder in step 2) is 2 to 5 μm;
[0015] In step 3), the mass ratio of the ordinary silicon powder to the ultrafine silicon powder is 5 to 7:1.
[0016] Preferably, the modifier solution in step 3) comprises a polymer solution and a coupling agent.
[0017] Preferably, the polymer solution comprises sodium lauryl sulfate solution, ammonium persulfate solution and pyrrole solution; and the coupling agent comprises two or three of vinyl bisstearamide, vinyl trimethoxysilane and vinyl trichlorosilane.
[0018] Preferably, the mass fraction of the sodium lauryl sulfate solution is 15-20%, and the mass of the sodium lauryl sulfate solution is 10-15‰ of the total mass of the ordinary silicon powder and the ultrafine silicon powder;
[0019] The mass fraction of the ammonium persulfate solution is 10-15%, and the mass of the ammonium persulfate solution is 6-9‰ of the total mass of the ordinary silicon micropowder and the ultrafine silicon micropowder;
[0020] The mass fraction of the pyrrole solution is 97-100%, and the mass of the pyrrole solution is 3-6‰ of the total mass of the ordinary silicon micropowder and the ultrafine silicon micropowder;
[0021] The mass of the coupling agent is 7-12‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder.
[0022] Preferably, in step 3), the modifier solution is mixed with ordinary silicon powder and ultrafine silicon powder by spraying, and the spray flow rate is 10 to 30 L / h;
[0023] The surface modification temperature is 90-120° C., and the surface modification time is 45-90 min. The surface modification is carried out under stirring conditions, and the stirring speed is 300-600 r / min.
[0024] The present invention also provides modified silicon micropowder prepared by the preparation method.
[0025] The present invention also provides application of the modified silicon micropowder in silicone rubber.
[0026] Beneficial effects of the present invention:
[0027] The present invention adopts a compound of two silicon micropowders with different particle sizes, which can form a more compact stacking of small-particle and large-particle silicon micropowders at a low filling amount, which is conducive to forming a more effective and compact heat conduction network and improving the thermal conductivity of the silicone rubber composite material; a unique modifier is used to modify the compounded silicon micropowder to improve the interface compatibility between the silicon micropowder and the silicone rubber matrix, while improving the thermal conductivity of the silicone rubber composite material, it can also ensure good mechanical properties; pyrrole itself is an intrinsic conductive polymer, and the use of a modifier containing pyrrole to modify the silicon micropowder can improve the electrical conductivity of the silicone rubber composite material while having no significant effect on the electrical insulation properties of the silicone rubber. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing modified silicon micropowder, comprising the following steps:
[0029] 1) Dry grinding the quartz ore particles to obtain ordinary silicon powder;
[0030] 2) Wet ball milling of ordinary silicon powder to obtain ultrafine silicon powder;
[0031] 3) Ordinary silicon micropowder, ultrafine silicon micropowder and modifier solution are mixed and surface modified to obtain modified silicon micropowder.
[0032] In the present invention, the diameter of the quartz ore particles in step 1) is preferably 5 to 10 cm, more preferably 6 to 9 cm, and more preferably 7 to 8 cm; the D50 particle size of ordinary silicon powder is preferably 16 to 19 μm, more preferably 17 to 18 μm.
[0033] In the present invention, the quartz ore particles in step 1) are preferably obtained by crushing quartz ore, and the mass content of silicon dioxide in the quartz ore is preferably ≥90%, and more preferably ≥93%.
[0034] In the present invention, the medium used in the wet ball milling in step 2) preferably comprises sodium polyacrylate, sodium hexametaphosphate and water, wherein the mass of the sodium polyacrylate is preferably 9-12‰ of the mass of ordinary silicon micropowder, more preferably 10-11‰, and more preferably 10.5‰; the mass of the sodium hexametaphosphate is preferably 4-7‰ of the mass of ordinary silicon micropowder, more preferably 5-6‰, and more preferably 5.5‰; the mass of water is preferably 5-10% of the mass of ordinary silicon micropowder, more preferably 6-9%, and more preferably 7-8%;
[0035] The rotation speed of the wet ball milling is preferably 60-80 r / min, more preferably 65-75 r / min, and more preferably 70 r / min; the time of the wet ball milling is preferably 100-150 min, more preferably 110-140 min, and more preferably 120-130 min.
[0036] In the present invention, the medium used in the wet ball milling in step 2) is preferably added in the form of a spray, and the spray flow rate is preferably 10 to 30 L / h, more preferably 15 to 25 L / h, and more preferably 20 L / h.
[0037] In the present invention, the wet ball milling in step 2) is preferably carried out using an all-ceramic ball mill; after the wet ball milling, the ball-milled material is preferably flash dried and then passed through an all-ceramic air flow classifier to obtain ultrafine silicon powder; the flash drying temperature is preferably 180-210°C, more preferably 190-200°C; the flash drying time is preferably 15-30 min, more preferably 20-25 min; the material of the classifying wheel and the inner wall of the pipeline of the all-ceramic air flow classifier is preferably all-ceramic material, and the classifying wheel is preferably six wheels; the operating frequency of the all-ceramic air flow classifier is preferably 60-80 Hz, more preferably 70 Hz.
[0038] In the present invention, the D50 particle size of the ultrafine silicon powder in step 2) is preferably 2 to 5 μm, more preferably 3 to 4 μm;
[0039] In step 3), the mass ratio of the ordinary silicon powder to the ultrafine silicon powder is preferably 5 to 7:1, more preferably 5.5 to 6.5:1, and more preferably 6:1.
[0040] In the present invention, the D100 particle size of the ultrafine silicon powder in step 2) is preferably 12 to 15 μm, more preferably 13 to 14 μm.
[0041] In the present invention, the modifier solution in step 3) preferably comprises a polymer solution and a coupling agent.
[0042] In the present invention, the polymer solution preferably comprises sodium lauryl sulfate solution, ammonium persulfate solution and pyrrole solution; the coupling agent preferably comprises two or three of vinyl bisstearamide, vinyl trimethoxysilane and vinyl trichlorosilane.
[0043] In the present invention, the mass fraction of the sodium lauryl sulfate solution is preferably 15-20%, more preferably 16-19%, and more preferably 17-18%; the mass of the sodium lauryl sulfate solution is preferably 10-15‰ of the total mass of the ordinary silicon powder and the ultrafine silicon powder, more preferably 11-14‰, and more preferably 12-13‰;
[0044] The mass fraction of the ammonium persulfate solution is preferably 10-15%, more preferably 11-14%, and more preferably 12-13%; the mass of the ammonium persulfate solution is preferably 6-9‰ of the total mass of the ordinary silicon micropowder and the ultrafine silicon micropowder, more preferably 7-8‰, and more preferably 7.5‰;
[0045] The mass fraction of the pyrrole solution is preferably 97-100%, more preferably 98-99%; the mass of the pyrrole solution is preferably 3-6‰ of the total mass of ordinary silicon powder and ultrafine silicon powder, more preferably 4-5‰, and more preferably 4.5‰;
[0046] The mass of the coupling agent is preferably 7-12‰ of the total mass of ordinary silicon powder and ultrafine silicon powder, more preferably 8-11‰, and even more preferably 9-10‰.
[0047] In the present invention, the coupling agent is preferably first hydrolyzed to obtain a coupling agent solution, and the coupling agent solution is then used for surface modification; the reagent used for hydrolysis preferably comprises anhydrous ethanol, glycerol and water, and the volume ratio of the coupling agent, anhydrous ethanol, glycerol and water is preferably 1:0.8~1.2:0.8~1.2:7~9, more preferably 1:0.9~1.1:0.9~1.1:7.5~8.5, and more preferably 1:1:1:8.
[0048] In the present invention, the modifier solution in step 3) is preferably mixed with ordinary silicon powder or ultrafine silicon powder by spraying, and the spray flow rate is preferably 10 to 30 L / h, more preferably 15 to 25 L / h, and more preferably 20 L / h;
[0049] The surface modification temperature is preferably 90-120°C, more preferably 100-110°C, and more preferably 105°C; the surface modification time is preferably 45-90 min, more preferably 60-80 min, and more preferably 70 min; the surface modification is preferably carried out under stirring conditions, and the stirring speed is preferably 300-600 r / min, more preferably 400-500 r / min, and more preferably 450 r / min.
[0050] The present invention also provides modified silicon micropowder prepared by the preparation method.
[0051] The present invention also provides application of the modified silicon micropowder in silicone rubber.
[0052] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0053] The quartz ore used in the embodiments of the present invention comes from Suichuan Jianji Mining.
[0054] Example 1
[0055] The medium used in the wet ball milling in this embodiment is composed of sodium polyacrylate, sodium hexametaphosphate and water. The mass of sodium polyacrylate is 9‰ of the mass of ordinary silicon micropowder, the mass of sodium hexametaphosphate is 5‰ of the mass of ordinary silicon micropowder, and the mass of water is 7% of the mass of ordinary silicon micropowder.
[0056] The modifier solution consists of a polymer solution and a coupling agent, and the polymer solution consists of a sodium dodecyl sulfate solution, an ammonium persulfate solution and a pyrrole solution, wherein the mass fraction of the sodium dodecyl sulfate solution is 20%, and the mass of the sodium dodecyl sulfate solution is 10‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the mass fraction of the ammonium persulfate solution is 12%, and the mass of the ammonium persulfate solution is 9‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the mass fraction of the pyrrole solution is 99%, and the mass of the pyrrole solution is 4‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the coupling agent consists of vinyl bisstearamide and vinyl trimethoxysilane in a mass ratio of 1:1, and the mass of the coupling agent is 8‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the volume ratio of the coupling agent, anhydrous ethanol, glycerol and water in the coupling agent solution is 1:1:1:7.
[0057] The preparation method of this embodiment is as follows:
[0058] Quartz ore with a silica content of 90% by mass was crushed and cleaned in a jaw crusher to produce quartz ore particles with a diameter of 6 cm. The quartz ore particles were then fed into a fully ceramic roller mill via an automatic feeder for grinding and sieving to produce ordinary silicon micropowder with a D50 particle size of 16 μm. The ordinary silicon micropowder was transferred via a powder delivery pipeline to a fully ceramic ball mill. The milling media was sprayed at the inlet of the mill at a rate of 30 L / h and wet-milled at a speed of 60 rpm for 150 minutes. The wet-milled material was classified in a fully ceramic air classifier (with six classifier wheels). The inlet velocity of the milled material and the airflow into the cyclone separator was 23 m / s, and the fully ceramic air classifier operated at a frequency of 70 Hz. The collected material was flash-dried in a flash dryer at 200°C for 15 minutes to produce ultrafine silicon micropowder with a D100 particle size of 14 μm and a D50 particle size of 4 μm. At 100°C, ordinary silicon micropowder and ultrafine silicon micropowder with a mass ratio of 7:1 were transported to a high-speed mixer through a metering pipe, and the modifier solution was sprayed at 15L / h. The surface modification was carried out at a speed of 600r / min for 45min to obtain modified silicon micropowder.
[0059] Five portions of modified silica powder were taken and the SiO2 content, oil absorption value, moisture, particle size and activation degree of the five portions of modified silica powder were tested. The SiO2 content was tested according to SJ / T 10675-2002, the oil absorption value was tested according to GB / T5211.15-2014, the moisture was tested according to GB / T 5211.3-2020, the particle size was tested according to GB / T19077-2016, and the activation degree was tested according to 3.19 in GB / T 19281-2014. The test results are shown in Table 1.
[0060] Table 1 Batch test results of modified silicon micropowder prepared in Example 1
[0061] Sample number 1 2 3 4 5 <![CDATA[SiO2 content / %]]> 92.3 92.4 92.1 92.4 92.3 Oil absorption value / mL / 100g 15.4 14.8 15.2 15.1 15.2 D50 / μm 13.89 13.92 13.91 13.93 13.95 Activation degree / % 98.68 98.72 98.79 98.81 98.79 Moisture / % 0.15 0.17 0.21 0.19 0.16
[0062] Example 2
[0063] The medium used in the wet ball milling in this embodiment is composed of sodium polyacrylate, sodium hexametaphosphate and water. The mass of sodium polyacrylate is 12‰ of the mass of ordinary silicon micropowder, the mass of sodium hexametaphosphate is 6‰ of the mass of ordinary silicon micropowder, and the mass of water is 8% of the mass of ordinary silicon micropowder.
[0064] The modifier solution consists of a polymer solution and a coupling agent, and the polymer solution consists of a sodium dodecyl sulfate solution, an ammonium persulfate solution and a pyrrole solution, wherein the mass fraction of the sodium dodecyl sulfate solution is 17%, and the mass of the sodium dodecyl sulfate solution is 15‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the mass fraction of the ammonium persulfate solution is 15%, and the mass of the ammonium persulfate solution is 7‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the mass fraction of the pyrrole solution is 99%, and the mass of the pyrrole solution is 6‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the coupling agent consists of vinyl bisstearamide and vinyl trimethoxysilane in a mass ratio of 1:1, and the mass of the coupling agent is 10‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the volume ratio of the coupling agent, anhydrous ethanol, glycerol and water in the coupling agent solution is 1:1:1:8.
[0065] The preparation method of this embodiment is as follows:
[0066] Quartz ore with a silica content of 92% by mass was crushed and cleaned in a jaw crusher to produce quartz ore particles with a diameter of 8 cm. The quartz ore particles were then fed into a fully ceramic roller mill via an automatic feeder for grinding and sieving to produce ordinary silicon micropowder with a D50 particle size of 17 μm. The ordinary silicon micropowder was transferred via a powder delivery pipeline to a fully ceramic ball mill. The milling media was sprayed at the inlet of the mill at a rate of 20 L / h and wet-milled at 70 rpm for 135 minutes. The wet-milled material was then classified in a fully ceramic air classifier (with six classifier wheels). The inlet velocity of the milled material and the airflow into the cyclone separator was 23 m / s, and the fully ceramic air classifier was operated at a frequency of 70 Hz. The collected material was flash-dried in a flash dryer at 180°C for 25 minutes to produce ultrafine silicon micropowder with a D100 particle size of 13 μm and a D50 particle size of 3 μm. At 120°C, ordinary silicon micropowder and ultrafine silicon micropowder with a mass ratio of 6:1 were transported to a high-speed mixer through a metering pipe, and the modifier solution was sprayed at 30L / h. The surface modification was carried out at a speed of 450r / min for 60min to obtain modified silicon micropowder.
[0067] Five portions of modified silica powder were taken and the SiO2 content, oil absorption value, moisture, particle size and activation degree of the five portions of modified silica powder were tested. The SiO2 content was tested according to SJ / T 10675-2002, the oil absorption value was tested according to GB / T5211.15-2014, the moisture was tested according to GB / T 5211.3-2020, the particle size was tested according to GB / T19077-2016, and the activation degree was tested according to 3.19 in GB / T 19281-2014. The test results are shown in Table 2.
[0068] Table 2 Batch test results of modified silicon micropowder prepared in Example 2
[0069] Sample number 1 2 3 4 5 <![CDATA[SiO2 content / %]]> 92.6 92.7 92.8 92.9 92.8 Oil absorption value / mL / 100g 15.9 15.6 15.9 15.8 15.7 D50 / μm 13.79 13.78 13.76 13.75 13.77 Activation degree / % 98.87 98.89 98.78 98.85 98.84 Moisture / % 0.14 0.13 0.16 0.17 0.18
[0070] Example 3
[0071] The medium used in the wet ball milling in this embodiment is composed of sodium polyacrylate, sodium hexametaphosphate and water. The mass of sodium polyacrylate is 10‰ of the mass of ordinary silicon micropowder, the mass of sodium hexametaphosphate is 7‰ of the mass of ordinary silicon micropowder, and the mass of water is 10% of the mass of ordinary silicon micropowder.
[0072] The modifier solution consists of a polymer solution and a coupling agent, and the polymer solution consists of a sodium dodecyl sulfate solution, an ammonium persulfate solution and a pyrrole solution, wherein the mass fraction of the sodium dodecyl sulfate solution is 15%, and the mass of the sodium dodecyl sulfate solution is 14‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the mass fraction of the ammonium persulfate solution is 10%, and the mass of the ammonium persulfate solution is 6‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the mass fraction of the pyrrole solution is 99%, and the mass of the pyrrole solution is 3‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the coupling agent consists of vinyl bisstearamide and vinyl trichlorosilane in a mass ratio of 1:1, and the mass of the coupling agent is 12‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder; the volume ratio of the coupling agent, anhydrous ethanol, glycerol and water in the coupling agent solution is 1:1:1:9.
[0073] The preparation method of this embodiment is as follows:
[0074] Quartz ore with a silica content of 92% by mass was crushed and cleaned in a jaw crusher to produce quartz ore particles with a diameter of 10 cm. The quartz ore particles were then fed into a fully ceramic roller mill via an automatic feeder for grinding and sieving to produce ordinary silicon micropowder with a D50 particle size of 19 μm. The ordinary silicon micropowder was transferred via a powder delivery pipeline to a fully ceramic ball mill. The milling media was sprayed at the inlet of the mill at 20 L / h and wet-milled at 80 rpm for 100 min. The wet-milled material was classified in a fully ceramic air classifier (with six classifier wheels). The inlet velocity of the milled material and the airflow into the cyclone separator was 23 m / s, and the fully ceramic air classifier operated at a frequency of 70 Hz. The collected material was flash-dried in a flash dryer at 210°C for 20 min, yielding ultrafine silicon micropowder with a D100 particle size of 12 μm and a D50 particle size of 2 μm. At 90°C, silicon micropowder and ultrafine silicon micropowder with a mass ratio of 5:1 were transported to a high-speed mixer through a metering pipe, the modifier solution was sprayed at 20L / h, and the surface modification was carried out at a speed of 300r / min for 90min to obtain modified silicon micropowder.
[0075] Five portions of modified silica powder were taken and the SiO2 content, oil absorption value, moisture, particle size and activation degree of the five portions of modified silica powder were tested. The SiO2 content was tested according to SJ / T 10675-2002, the oil absorption value was tested according to GB / T5211.15-2014, the moisture was tested according to GB / T 5211.3-2020, the particle size was tested according to GB / T19077-2016, and the activation degree was tested according to 3.19 in GB / T 19281-2014. The test results are shown in Table 3.
[0076] Table 3 Batch test results of modified silicon micropowder prepared in Example 3
[0077] Sample number 1 2 3 4 5 <![CDATA[SiO2 content / %]]> 92.4 92.6 92.7 92.8 92.8 Oil absorption value / mL / 100g 15.9 15.8 15.9 15.8 15.8 D50 / μm 13.82 13.83 13.86 13.83 13.85 Activation degree / % 98.85 98.87 98.86 98.86 98.85 Moisture / % 0.16 0.15 0.17 0.16 0.16
[0078] Application Example 1
[0079] In parts by mass, 100 parts of methyl vinyl silicone rubber (PS02, Shenzhen Senri Silicone Materials Co., Ltd.), 20 parts of EPDM rubber (SABIC657, ethylene content of 73%, Saudi Basic Industries Corporation), 30 parts of modified microsilica powder prepared in Example 1, 3.5 parts of stearic acid, 5 parts of zinc oxide, 1.5 parts of rubber accelerator DM, 1.5 parts of rubber accelerator TMTD, 1.5 parts of antioxidant 4010, 5 parts of paraffin oil and 2 parts of vulcanizing agent di-tert-butyl peroxyhexane were mixed, mixed in a mixing chamber at 50°C for 20 minutes, and then vulcanized at 180°C. After reaching a vulcanization degree of 90%, vulcanization was continued for 2 minutes. The total vulcanization time was 20 minutes to obtain a silicone rubber composite material.
[0080] Application Example 2
[0081] The modified microsilica powder in Application Example 1 was replaced by the modified microsilica powder prepared in Example 2, and the rest was the same as in Application Example 1.
[0082] Application Example 3
[0083] The modified microsilica powder in Application Example 1 was replaced by the modified microsilica powder prepared in Example 3, and the rest was the same as in Application Example 1.
[0084] Comparative Application Example 1
[0085] The modified microsilica powder in Application Example 1 was replaced with microsilica powder GS-400 produced by Jiangxi Guangyuan Chemical Co., Ltd., and the rest was the same as in Application Example 1.
[0086] Application Comparative Example 2
[0087] The modified microsilica powder in Application Example 1 was replaced with microsilica powder GS-3000 produced by Jiangxi Guangyuan Chemical Co., Ltd., and the rest was the same as in Application Example 1.
[0088] Application Comparative Example 3
[0089] The modified silicon powder in Application Example 1 is omitted, and the rest is the same as Application Example 1.
[0090] The performance tests were conducted on the silicone rubber composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively. The test results are shown in Table 4.
[0091] Tensile strength and elongation at break tests were conducted in accordance with GB / T 528-2009;
[0092] Conduct abrasion index test in accordance with GB / T 1689-2014;
[0093] Carry out volume resistivity and surface resistivity tests in accordance with GB / T 2439-2001;
[0094] Using LEA447 Nano The thermal conductivity was measured by a flash thermal conductivity analyzer at 30°C.
[0095] Table 4 Performance test results of silicone rubber composite materials
[0096]
[0097] As can be seen from Table 4, compared with the unmodified single particle size silicon micropowder, the modified silicon micropowder of the present invention with different particle sizes can improve the interfacial compatibility between the silicon micropowder and the silicone rubber matrix, improve the mechanical properties of the silicone rubber composite material, and at the same time improve the thermal conductivity of the silicone rubber composite material; the pyrrole in the modifier solution itself is an intrinsic conductive polymer. After the silicon micropowder is modified, the conductive properties of the silicone rubber composite material are improved while the electrical insulation properties are not significantly affected; when the modified silicon micropowder of the present invention is added to the silicone rubber, the wear index of the silicone rubber composite material is improved, which may be because the silicon micropowder with different particle sizes increases the density of the rubber in the rubber matrix and improves the wear resistance.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing modified silicon micropowder, characterized in that: The following steps are included: 1) Dry grinding the quartz ore particles to obtain ordinary silicon powder; 2) Wet ball milling of ordinary silicon powder to obtain ultrafine silicon powder; 3) Ordinary silicon micropowder, ultrafine silicon micropowder and modifier solution are mixed and surface modified to obtain modified silicon micropowder.
2. The preparation method according to claim 1, characterized in that In step 1), the diameter of the quartz ore particles is 5 to 10 cm, and the D50 particle size of ordinary silicon powder is 16 to 19 μm.
3. The preparation method according to claim 1 or 2, characterized in that Step 2) The medium used in the wet ball milling comprises sodium polyacrylate, sodium hexametaphosphate and water, wherein the mass of the sodium polyacrylate is 9-12‰ of the mass of ordinary silicon micropowder, the mass of the sodium hexametaphosphate is 4-7‰ of the mass of ordinary silicon micropowder, and the mass of the water is 5-10% of the mass of ordinary silicon micropowder; The rotation speed of the wet ball mill is 60-80 r / min, and the time of the wet ball mill is 100-150 min.
4. The preparation method according to claim 3, characterized in that Step 2) The D50 particle size of the ultrafine silicon powder is 2 to 5 μm; In step 3), the mass ratio of the ordinary silicon powder to the ultrafine silicon powder is 5 to 7:
1.
5. The preparation method according to claim 4, characterized in that Step 3) The modifier solution comprises a polymer solution and a coupling agent.
6. The preparation method according to claim 5, characterized in that The polymer solution comprises sodium lauryl sulfate solution, ammonium persulfate solution and pyrrole solution; and the coupling agent comprises two or three of vinyl bisstearamide, vinyl trimethoxysilane and vinyl trichlorosilane.
7. The preparation method according to claim 6, characterized in that The mass fraction of the sodium lauryl sulfate solution is 15-20%, and the mass of the sodium lauryl sulfate solution is 10-15‰ of the total mass of the ordinary silicon powder and the ultrafine silicon powder; The mass fraction of the ammonium persulfate solution is 10-15%, and the mass of the ammonium persulfate solution is 6-9‰ of the total mass of the ordinary silicon micropowder and the ultrafine silicon micropowder; The mass fraction of the pyrrole solution is 97-100%, and the mass of the pyrrole solution is 3-6‰ of the total mass of the ordinary silicon micropowder and the ultrafine silicon micropowder; The mass of the coupling agent is 7-12‰ of the total mass of ordinary silicon micropowder and ultrafine silicon micropowder.
8. The preparation method according to claim 7, characterized in that Step 3) The modifier solution is mixed with ordinary silicon powder and ultrafine silicon powder by spraying, and the spray flow rate is 10 to 30 L / h; The surface modification temperature is 90-120° C., and the surface modification time is 45-90 min. The surface modification is carried out under stirring conditions, and the stirring speed is 300-600 r / min.
9. Modified silicon micropowder prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the modified silicon micropowder according to claim 9 in silicone rubber.